1999
DOI: 10.1074/jbc.274.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Influx Factor, Further Evidence It Is 5,6-Epoxyeicosatrienoic Acid

Abstract: We present evidence in astrocytes that 5,6-epoxyeicosatrienoic acid, a cytochrome P450 epoxygenase metabolite of arachidonic acid, may be a component of calcium influx factor, the elusive link between release of Ca 2؉ from intracellular stores and capacitative Ca 2؉ influx. Capacitative influx of extracellular Ca 2؉ was inhibited by blockade of the two critical steps in epoxyeicosatrienoic acid synthesis: release of arachidonic acid from phospholipid stores by cytosolic phospholipase A 2 and cytochrome P450 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
94
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 45 publications
9
94
1
1
Order By: Relevance
“…This observation is consistent with our previous findings that demonstrated the ability of glutamate to stimulate release of EETs from astrocytes (Alkayed et al, 1997). In vivo, EETs may act to increase K Ca channel activity directly or may act indirectly as a calcium influx factor (Rziglinski et al, 1999) to replenish Ca 2ϩ stores necessary to sustain an increased Ca 2ϩ level for K Ca channel activation. The results of the present study in astrocytes together with the previous work on isolated vascular smooth muscle cells (Gebremedhin et al, 1992) implicate the ability of EETs to act on K Ca channels.…”
Section: Discussionsupporting
confidence: 82%
“…This observation is consistent with our previous findings that demonstrated the ability of glutamate to stimulate release of EETs from astrocytes (Alkayed et al, 1997). In vivo, EETs may act to increase K Ca channel activity directly or may act indirectly as a calcium influx factor (Rziglinski et al, 1999) to replenish Ca 2ϩ stores necessary to sustain an increased Ca 2ϩ level for K Ca channel activation. The results of the present study in astrocytes together with the previous work on isolated vascular smooth muscle cells (Gebremedhin et al, 1992) implicate the ability of EETs to act on K Ca channels.…”
Section: Discussionsupporting
confidence: 82%
“…Arachidonic acid (20:4) facilitates Ca 2ϩ entry from the extracellular space and Ca 2ϩ release from ER (42), and 20:4-containing plasmenylethanolamine species are abundant in ER and are excellent iPLA 2 ␤ substrates (43). Moreover, Ca 2ϩ influx factor is an arachidonate oxygenation product (44), and its production could involve iPLA 2 ␤ action.…”
Section: Discussionmentioning
confidence: 99%
“…Also in cultured cortical astrocytes, TRPV4 channels form complexes with aquaporin 4 to regulate cell volume responses to hypoosmotic stress (12). Notably, it has been shown that TRPV4 channels in other preparations are activated by epoxyeicosatrienoic acids (EETs) (13-15), which have been implicated in NVC (16-18) and reportedly stimulate Ca 2+ influx in rat cortical astrocytes (19,20). TRPV4 channels are thermosensitive, osmosensitive, and mechanosensitive, and thereby mediate processes by which cells sense and respond to environmental cues (21)(22)(23)(24) (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%